Challenges and future prospects of antibiotic therapy: from peptides to phages utilization - Mandal, Santi M.; Roy, Anupam; Ghosh, Ananta K.; Hazra, Tapas K.; Basak, Amit; Franco, Octavio L. (Frontiers in Pharmacology, 2014)
Bacterial infections are raising serious concern across the globe. The effectiveness of conventional antibiotics is decreasing due to global emergence of multi-drug-resistant (MDR) bacterial pathogens. This process seems to be primarily caused by an indiscriminate and inappropriate use of antibiotics in non-infected patients and in the food industry. New classes of antibiotics with different actions against MDR pathogens need to be developed urgently. In this context, this review focuses on several ways and future directions to search for the next generation of safe and effective antibiotics compounds including antimicrobial peptides, phage therapy, phytochemicals, metalloantibiotics, LPS and efflux pump inhibitors to control the infections caused by MDR pathogens.